Synthesis of bioactive cyclohexenyl chalcones and flavonoid derivatives / Chee Chin Fei - Chee, Chin Fei (2011)
Flavonoids are a class of natural products that are well known to possess a wide range of pharmacological properties. Due to their recent discovery in modulating muscarinic receptor activity and its inhibitory effect against dengue-2 virus NS3 protease, flavonoids are idea candidates for drug development. This dissertation describes the syntheses of several flavones and some Diels-Alder adducts derived from chalcones. A modified Baker-Venkataraman method has been developed where flavones were prepared in a one-pot procedure from the corresponding 2-hydroxyacetophenones and acyl chlorides under different conditions. When 2-hydroxyacetophenone is heated with a stoichiometric amount of acyl chloride, either in a DBU/pyridine system or in an open K2CO3/acetone system, only the flavone is obtained, albeit in modest yield. However, when it is heated with an excess of acyl chloride in a DBU/pyridine system, the 3-acylflavone is the only product, while treatment in an open K2CO3/acetone system afforded the flavone as the major product and a smaller amount of 3-aroylflavone. Panduratin A and its regioisomer isopanduratin A have been synthesized in four steps from (E)-ocimene, [(E)-3,7-dimethyl-1,3,6-octatriene] via a Diels–Alder cycloaddition reaction. An overall yield of 75% was achieved from 2,6-dihydroxy,4-methoxyacetophenone. The mulberry Diels-Alder adducts pentamethyl ethers of the kuwanon V and dorsterone have been synthesised via a biomimetic intermolecular [4+2] cycloaddition reaction between a highly electron-rich dienophile and a Lewis acid sensitive diene derived from chalcone. Cycloaddition reaction under thermal condition afforded the kuwanon V and dorsterone in a 3:2 ratio. Cycloaddition catalysed by AgOTf/Bu4NBH4 gave higher yield of adducts.